Comparison of Tibiofemoral and Patellofemoral Mobilization in Improving Pain, Rom and Functional Disability in Patellofemoral Pain Syndrome (British Journal of Multidisciplinary and Advanced Studies, 2025)
Patellofemoral pain syndrome significantly impacts daily activities in adults. Physical therapy, including targeted exercises and both patellofemoral and tibiofemoral mobilization techniques, is a primary treatment approach for managing this condition.This study aimed to compare the effects of tibiofemoral and patellofemoral mobilization on pain, range of motion (ROM), and functional disability in patients with patellofemoral pain syndrome.A randomized controlled trial was conducted on 68 participants (n=34) at the Physiotherapy Department of Doctors Clinic, Samnabad, Lahore. The patients were randomly assigned into two groups: Group A received conventional treatment along with patellofemoral mobilization, while Group B received conventional treatment combined with tibiofemoral mobilization. The study spanned six months, with assessments conducted prior to treatment and weekly thereafter. Numeric Pain Rating Scale (NPRS) for pain, a goniometer for knee range of motion, and the Kujala scoring system for functional status used for assessment. The study results demonstrated significant improvements in NPRS scores, range of motion, and Kujala scores in both groups, with a p-value of 0.000. However, a comparison between the groups confirmed that conventional physiotherapy combined with patellofemoral mobilization yielded superior outcomes in reducing pain, improving range of motion, and enhancing functional status compared to tibiofemoral mobilization, with a p-value of